Flexible solid-state lithium ion battery and preparation method thereof
By depositing diamond films on the positive and negative surfaces of flexible solid lithium-ion batteries and using multi-element doped porous carbon materials, the problems of large interface impedance, insufficient stability, low ionic conductivity and insufficient energy density of flexible solid lithium-ion batteries are solved, and efficient electrochemical performance and excellent weathering resistance are achieved.
Patent Information
- Application Number
- CN202411748508.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing flexible solid-state lithium-ion batteries have problems such as large interface impedance, insufficient interface stability, low ion conductivity and insufficient energy density, which limits their application in high power demand scenarios.
By depositing diamond films on the surfaces of the positive and negative electrodes, and using multi-element (phosphorus, sulfur, silicon, boron and nitrogen) doped porous carbon materials as the negative electrode materials, the ionic conductivity and energy density of the battery are improved, while enhancing interface stability and reducing interface impedance.
The high ion conductivity, high energy density, excellent interface stability and small interface impedance of flexible solid lithium-ion batteries are achieved, improving the rate performance and cycle stability of the battery.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and more specifically relates to a flexible solid-state lithium ion battery and a preparation method thereof. Background Art
[0002] With the advancement of science and technology, electronic devices are constantly developing towards thinness, diversification and flexibility. The rise of smart hardware such as foldable mobile phones and wearable devices has created an urgent need for flexible energy storage devices to match them. Traditional rigid lithium-ion batteries cannot meet the requirements of these devices when they are bent, folded or deformed, which limits the further development of flexible electronic devices.
[0003] As a result, flexible solid-state lithium-ion batteries have been developed in all aspects. Existing flexible solid-state lithium-ion batteries have the following defects: 1. Interface problems: (1) Excessive interface impedance: The solid electrolyte and the electrode material are in solid-solid contact, the effective contact between the electrode and the electrolyte is weak, and the ion transmission kinetics in the solid material is low, resulting in a large interface impedance, which will affect the battery's charging and discharging efficiency and performance. (2) Insufficient interface stability: During the battery charging and discharging process, the electrode material may undergo volume changes, resulting in stress at the interface between the electrode and the electrolyte. Long-term use may cause cracks and separation at the interface, affecting the battery's cycle life and safety. 2. Performance: (1) Low ionic conductivity: Compared with liquid electrolytes, the ionic conductivity of solid electrolytes is generally not high, which makes the battery's internal resistance larger, the charging and discharging speed slow, and the overall rate performance low, limiting its application in high-power demand scenarios, such as fast charging of electric vehicles. (2) Energy density needs to be improved: Although solid-state batteries have a higher energy density in theory, the energy density of flexible solid-state lithium-ion batteries currently under development and production is still far from expectations, making it difficult to meet the needs of some devices with extremely high requirements for battery life. Therefore, developing a flexible solid-state lithium-ion battery with high ionic conductivity, high energy density, excellent interface stability, and low interface impedance is of great significance to the development of flexible solid-state batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a flexible solid-state lithium-ion battery and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art and realize the preparation of a flexible solid-state lithium-ion battery with high ionic conductivity, high energy density, excellent interface stability and small interface impedance.
[0005] To achieve the above object, the present invention provides the following solutions: One of the technical solutions of the present invention is to provide a flexible solid-state lithium-ion battery, which comprises a solid positive electrode, a solid negative electrode and a solid electrolyte; the solid positive electrode is a lithium foil coated with a diamond film; the solid negative electrode comprises a composite negative electrode coated with a diamond film, a conductive agent, a lithium salt and a binder; the solid electrolyte comprises a polyethylene oxide-based solid polymer electrolyte or a polyvinylidene fluoride solid polymer electrolyte; and the composite negative electrode is prepared from coal gangue, boric acid and chitosan.
[0006] Preferably, the preparation of the composite negative electrode comprises the following steps: 1) Carbonizing and activating the coal gangue in sequence to obtain porous carbon; 2) dissolving boric acid and chitosan in an alcohol aqueous solution to obtain a mixed solution; immersing the obtained porous carbon in the mixed solution, and then heat-treating the mixture to obtain the composite negative electrode.
[0007] The present invention prepares a composite negative electrode from coal gangue. Coal gangue is a common solid waste. The present invention turns waste into treasure and utilizes phosphorus, sulfur and silicon elements rich in coal gangue to prepare porous carbon doped with phosphorus, sulfur and silicon. Among them, phosphorus doped into porous carbon can change the electronic structure and surface properties of carbon materials, increase the degree of defects in materials, thereby providing more lithium ion storage sites, which is beneficial to improving the specific capacity of batteries. At the same time, phosphorus can also enhance the compatibility between porous carbon and electrolyte, promote the transmission of lithium ions at the electrode / electrolyte interface, and improve the rate performance and cycle stability of batteries. The doping of sulfur can Increasing the interlayer distance between carbon materials is beneficial to the storage of lithium ions and the embedding and de-embedding process between carbon layers, thereby improving the rate performance of lithium-ion batteries, and significantly improving the battery specific capacity and cycle performance; Silicon and carbon have similar chemical properties, but the radius of silicon atoms is larger than that of carbon atoms. Silicon doped into porous carbon can increase the interlayer distance of carbon materials and provide more favorable channels for the embedding and de-embedding of lithium ions, thereby improving the diffusion rate of lithium ions and the rate performance of the battery; At the same time, the theoretical specific capacity of silicon is relatively high, and an appropriate amount of silicon doping can also increase the specific capacity of the negative electrode material, thereby improving the energy density of the battery.
[0008] The present invention then loads boric acid and chitosan into porous carbon. Since the porous carbon is activated porous carbon, its surface contains a large number of active groups (hydroxyl, carboxyl, etc.), which significantly improves the loading effect of boric acid and chitosan. After heat treatment, boron and nitrogen are doped into the porous carbon, thereby preparing a porous carbon material doped with multiple elements (phosphorus, sulfur, silicon, boron and nitrogen). Boron doping can adjust the energy band structure of the porous carbon and improve its conductivity and electrochemical activity. The presence of boron atoms can form a local uneven charge distribution in the carbon material, which is conducive to attracting lithium ions, improving the adsorption energy and diffusion rate of lithium ions, thereby improving the charge and discharge performance and rate performance of the battery. In addition, boron doping can also enhance the structural stability of the porous carbon, reduce the volume change during the charge and discharge process, and improve the cycle life of the battery. The introduction of nitrogen atoms can disrupt the π conjugated electron system of carbon atoms, thereby providing a larger electrochemical active area and more active sites, which can synergistically promote the charge transfer between carbon atoms and heteroatoms, and improve the conductivity and specific capacity of the carbon layer material.
[0009] The composite negative electrode prepared by the present invention has excellent electrochemical performance, so that the prepared flexible solid-state lithium ion battery has the characteristics of high ion conductivity and high energy density.
[0010] In addition, the present invention ensures that the flexible solid-state lithium-ion battery has the characteristics of excellent interface stability and low interface impedance by depositing a diamond film on the surface of the positive electrode and the negative electrode. During the deposition of the diamond film, under the action of hydrogen, methane, ethanol and anisole will generate CH3, CH2, H and O, wherein most of CH3 forms a diamond phase, CH2 and a small part of CH3 form a non-diamond phase, and the generated H and O etch the formed non-diamond phase to a certain extent. After subsequent calcination, the formed diamond film has a uniform pore structure; it will not affect the embedding and extraction of lithium ions, and will also avoid the problem of quality degradation of electrode materials due to volume changes; at the same time, the diamond film can also play the following roles: (1) improving the surface performance of the electrode: the diamond film has high hardness and Chemical stability: Depositing a diamond film on the electrode surface can make the electrode surface flatter and smoother, reduce the roughness and defects of the electrode surface, which helps the electrolyte to better contact the electrode, improve the uniformity and tightness of the contact, and thus increase the effective contact area; (2) Enhance electrode conductivity: Diamond has a certain conductivity. Covering the electrode with a diamond film can improve the conductivity of the electrode, reduce the resistance of the electrode, make the charge transfer between the electrode and the electrolyte easier, and facilitate the transmission of lithium ions between the electrode and the electrolyte, indirectly enhancing the effective contact between the two; (3) Improve the bonding strength between the electrolyte and the electrode: The surface of the diamond film contains rich active groups, which can ensure the close bonding between the electrolyte and the electrode material, significantly improve the interface stability, and reduce the interface impedance.
[0011] Preferably, the particle size of the coal gangue is 200-300 μm.
[0012] Preferably, the carbonization is carried out under an inert gas atmosphere, the inert gas includes nitrogen; the carbonization temperature is 800~900°C, and the carbonization time is 1~3h; the activation includes: placing the carbonization product in an acid solution for treatment, the acid solution includes one or more of acetic acid, hydrochloric acid and sulfuric acid, and the treatment time is 1~2h.
[0013] Preferably, the alcohol in the alcohol aqueous solution includes one or more of ethylene glycol, propylene glycol and butanediol; in the mixed solution, the mass fractions of the substances are: chitosan 2-4%, boric acid 2-4%, alcohol 60-85%, and the rest is water.
[0014] Preferably, the immersion time is 5 to 8 hours; the heat treatment temperature is 100 to 150° C., and the heat treatment time is 40 to 80 minutes.
[0015] Preferably, the conductive agent includes acetylene black, graphene or carbon fiber; the lithium salt includes lithium perchlorate and / or lithium tetrafluoroborate; and the binder includes polyvinylidene fluoride.
[0016] The second technical solution of the present invention is to provide a method for preparing the flexible solid-state lithium-ion battery, comprising the following steps: (1) mixing a composite negative electrode, a conductive agent, a lithium salt, a binder and a solvent to obtain an electrode slurry, coating the electrode slurry on a copper foil to obtain a negative electrode sheet, depositing a diamond film on the negative electrode sheet and calcining it to obtain a solid negative electrode; (2) Take lithium foil, deposit a diamond film on the surface of the lithium foil and calcine it to obtain a solid positive electrode; (3) The solid-state negative electrode, the solid-state electrolyte and the solid-state positive electrode are stacked and assembled to obtain the flexible solid-state lithium-ion battery.
[0017] Preferably, the solvent comprises N-methylpyrrolidone; the mass volume ratio of the composite negative electrode, conductive agent, lithium salt, binder and solvent is 8~9g:1~2g:1~3g:2~3g:20~40mL; and the coating thickness is 30~60μm.
[0018] Preferably, the deposition parameters are independently as follows: the deposition is carried out under a hydrogen atmosphere, the carbon sources are methane, ethanol and anisole, the volume ratio of methane, ethanol and anisole is 5-6:0.5-0.8:0.1-0.2, the flow rate of the carbon source is 15-30sccm, the surface temperature of the negative electrode sheet and the lithium foil during deposition is 700-800°C, the deposition pressure is 5-6kPa, and the deposition time is 1-2h; the calcination temperature is independently 800-900°C, and the calcination time is 30-80min.
[0019] The present invention discloses the following technical effects: 1. The present invention prepares a porous carbon material doped with multiple elements (phosphorus, sulfur, silicon, boron and nitrogen) through a specific process, and using it as a negative electrode material can realize the preparation of a flexible solid-state lithium-ion battery with high ion conductivity and high energy density; 2. The present invention deposits a diamond film on the surface of a solid positive electrode and a solid negative electrode, which can significantly improve the solid-solid interface stability and reduce the interface impedance; 3. The preparation process of the present invention is simple, and the raw materials used are simple and easy to obtain, which is suitable for large-scale promotion and application. DETAILED DESCRIPTION
[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0021] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0022] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0023] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0024] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0025] Example 1 Preparation of composite negative electrode: 1) Coal gangue with a particle size of 200 μm was first placed in a carbonization furnace for carbonization. Before carbonization, nitrogen was used to exhaust the air in the carbonization furnace. The carbonization temperature was 850 ° C and the carbonization time was 2 h. The carbonized product was then taken out and air-cooled to room temperature. It was then placed in a 35% hydrochloric acid aqueous solution for activation for 1 h, washed with deionized water for 3 times, and dried to obtain porous carbon. 2) preparing a mixed solution, wherein the mass fractions of the substances in the mixed solution are: chitosan 2%, boric acid 2%, ethylene glycol 85%, and the rest is deionized water; immersing the obtained porous carbon in the mixed solution for 6 hours, and then heat-treating it at 120°C for 1 hour to obtain a composite negative electrode; Preparation of flexible solid-state lithium-ion batteries: (1) The obtained composite negative electrode, graphene, lithium tetrafluoroborate, polyvinylidene fluoride and N-methylpyrrolidone were mixed in a dosage ratio of 8 g:1 g:2 g:2 g:35 mL to obtain an electrode slurry, the electrode slurry was coated on a copper foil with a coating thickness of 40 μm to obtain a negative electrode sheet, a diamond film was deposited on the negative electrode sheet, and then calcined at 800 ° C for 40 min to obtain a solid negative electrode; (2) Take lithium foil, deposit a diamond film on the surface of the lithium foil and calcine it at 850°C for 30 minutes to obtain a solid positive electrode; (3) stacking and assembling the solid negative electrode, solid electrolyte and solid positive electrode to obtain a flexible solid-state lithium-ion battery; The deposition parameters in steps (1) and (2) are as follows: the deposition is carried out under a hydrogen atmosphere, the carbon sources are methane, ethanol and anisole, the volume ratio of methane, ethanol and anisole is 5:0.5:0.1, the flow rate of the carbon source is 20 sccm, the surface temperature of the negative electrode sheet and the lithium foil during deposition is 750°C, the deposition pressure is 5 kPa, and the deposition time is 1 h.
[0026] The obtained flexible solid-state lithium-ion battery was charged and discharged under the conditions of 25°C, 0.05C current, and charge and discharge cut-off voltage of 0.005~2.0V. The results showed that after 20 cycles, the discharge capacity was above 452mAh / g, and the capacity retention rate reached 100%.
[0027] The obtained flexible solid-state lithium-ion battery was fully charged at 25°C, 0.05C current, and a charge and discharge cut-off voltage of 4.2~3.0V. After being bent 800 times, the charge and discharge test was carried out. The results showed that the battery charged and discharged normally and the capacity remained above 99.5%.
[0028] Example 2 Preparation of composite negative electrode: 1) Coal gangue with a particle size of 250 μm was first placed in a carbonization furnace for carbonization. Before carbonization, nitrogen was used to exhaust the air in the carbonization furnace. The carbonization temperature was 800 °C and the carbonization time was 1.5 h. The carbonized product was then taken out and air-cooled to room temperature. It was then placed in a 35% hydrochloric acid aqueous solution for activation for 1 h, washed with deionized water for 3 times, and dried to obtain porous carbon. 2) preparing a mixed solution, wherein the mass fractions of the substances in the mixed solution are: chitosan 3%, boric acid 2%, ethylene glycol 70%, and the rest is deionized water; immersing the obtained porous carbon in the mixed solution for 6 hours, and then heat-treating it at 120°C for 1 hour to obtain a composite negative electrode; Preparation of flexible solid-state lithium-ion batteries: (1) The obtained composite negative electrode, graphene, lithium tetrafluoroborate, polyvinylidene fluoride and N-methylpyrrolidone were mixed in a dosage ratio of 8.5 g:1 g:2 g:2 g:40 mL to obtain an electrode slurry, the electrode slurry was coated on a copper foil with a coating thickness of 35 μm to obtain a negative electrode sheet, a diamond film was deposited on the negative electrode sheet, and then calcined at 800° C. for 40 min to obtain a solid negative electrode; (2) Take lithium foil, deposit a diamond film on the surface of the lithium foil and calcine it at 850°C for 30 minutes to obtain a solid positive electrode; (3) stacking and assembling a solid negative electrode, a solid electrolyte and a solid positive electrode to obtain the flexible solid-state lithium-ion battery; The deposition parameters in steps (1) and (2) are as follows: the deposition is carried out under a hydrogen atmosphere, the carbon sources are methane, ethanol and anisole, the volume ratio of methane, ethanol and anisole is 5:0.7:0.2, the flow rate of the carbon source is 20 sccm, the surface temperature of the negative electrode sheet and the lithium foil during deposition is 700°C, the deposition pressure is 5 kPa, and the deposition time is 1.5 h.
[0029] The obtained flexible solid-state lithium-ion battery was charged and discharged under the conditions of 25°C, 0.05C current, and charge and discharge cut-off voltage of 0.005~2.0V. The results showed that after 20 cycles, the discharge capacity was above 439mAh / g, and the capacity retention rate reached 100%.
[0030] The obtained flexible solid-state lithium-ion battery was fully charged at 25°C, 0.05C current, and a charge and discharge cut-off voltage of 4.2~3.0V. After being bent 800 times, the charge and discharge test was carried out. The results showed that the battery charged and discharged normally and the capacity remained above 99.4%.
[0031] Comparative Example 1 The difference from Example 1 is that the addition of boric acid is omitted during the preparation of the composite negative electrode, and the rest is the same as Example 1.
[0032] The obtained flexible solid-state lithium-ion battery was charged and discharged under the conditions of 25°C, 0.05C current, and charge and discharge cut-off voltage of 0.005~2.0V. The results showed that after 20 cycles, the discharge capacity was above 324mAh / g, and the capacity retention rate reached 95%.
[0033] The obtained flexible solid-state lithium-ion battery was fully charged at 25°C, 0.05C current, and a charge and discharge cut-off voltage of 4.2~3.0V. After being bent 800 times, the charge and discharge test was carried out. The results showed that the battery charged and discharged normally and the capacity remained above 85.2%.
[0034] Comparative Example 2 The difference from Example 1 is that the addition of chitosan is omitted during the preparation of the composite negative electrode, and the rest is the same as Example 1.
[0035] The obtained flexible solid-state lithium-ion battery was charged and discharged under the conditions of 25°C, 0.05C current, and charge and discharge cut-off voltage of 0.005~2.0V. The results showed that after 20 cycles, the discharge capacity was above 339mAh / g, and the capacity retention rate reached 95%.
[0036] The obtained flexible solid-state lithium-ion battery was fully charged at 25°C, 0.05C current, and a charge and discharge cut-off voltage of 4.2~3.0V. After being bent 800 times, the charge and discharge test was carried out. The results showed that the battery charged and discharged normally and the capacity remained above 86.1%.
[0037] Comparative Example 3 The difference from Example 1 is that step 1) is omitted in the process of preparing the composite negative electrode, and the "porous carbon" in step 2) is replaced by "graphene", and the rest is the same as Example 1.
[0038] The obtained flexible solid-state lithium-ion battery was charged and discharged under the conditions of 25°C, 0.05C current, and charge and discharge cut-off voltage of 0.005~2.0V. The results showed that after 20 cycles, the discharge capacity was above 298mAh / g, and the capacity retention rate reached 89.2%.
[0039] The obtained flexible solid-state lithium-ion battery was fully charged at 25°C, 0.05C current, and a charge and discharge cut-off voltage of 4.2~3.0V. After being bent 800 times, the charge and discharge test was carried out. The results showed that the battery charged and discharged normally and the capacity remained above 76.5%.
[0040] Comparative Example 4 The difference from Example 1 is that the deposition of the diamond film is omitted during the preparation of the flexible solid-state lithium-ion battery, and the rest is the same as Example 1.
[0041] The obtained flexible solid-state lithium-ion battery was charged and discharged under the conditions of 25°C, 0.05C current, and charge and discharge cut-off voltage of 0.005~2.0V. The results showed that after 20 cycles, the discharge capacity was above 384mAh / g, and the capacity retention rate reached 98%.
[0042] The obtained flexible solid-state lithium-ion battery was fully charged at 25°C, 0.05C current, and a charge and discharge cut-off voltage of 4.2~3.0V. After being bent 800 times, the charge and discharge test was carried out. The results showed that the battery charged and discharged normally and the capacity remained above 68.1%.
[0043] The batteries obtained in the above examples and comparative examples were subjected to low temperature freezing test and high temperature treatment test to test their weather resistance: Test method: Low temperature freezing test: put the battery into a freezer at -30℃ for 1 hour, take it out and connect the battery to the LED bulb through a wire to observe whether the LED bulb can work normally. The results show that the batteries obtained in Examples 1-2 and Comparative Examples 1-3 can make the LED bulb work normally, while the LED bulb connected to the battery obtained in Comparative Example 4 is not lit.
[0044] High temperature treatment test: Wrap the battery with plastic film and place it in 45℃ hot water. After 1 hour of treatment, take it out and connect the battery to the LED bulb through a wire to observe whether the LED bulb can work normally. The results show that the batteries obtained in Examples 1-2 and Comparative Examples 1-2 can make the LED bulb work normally, while the LED bulb connected to the battery obtained in Comparative Example 3 lights up continuously for 5 minutes and then goes out, and the LED bulb connected to the battery obtained in Comparative Example 4 is not lit.
[0045] It can be seen from this that the battery obtained by the present invention has excellent weather resistance.
[0046] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0047] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A flexible solid-state lithium-ion battery, characterized in that: The flexible solid-state lithium-ion battery comprises a solid positive electrode, a solid negative electrode and a solid electrolyte; the solid positive electrode is a lithium foil coated with a diamond film; the solid negative electrode comprises a composite negative electrode coated with a diamond film, a conductive agent, a lithium salt and a binder; the solid electrolyte comprises a polyethylene oxide-based solid polymer electrolyte or a polyvinylidene fluoride solid polymer electrolyte; and the composite negative electrode is prepared from coal gangue, boric acid and chitosan.
2. The flexible solid-state lithium-ion battery according to claim 1, characterized in that: The preparation of the composite negative electrode comprises the following steps: 1) Carbonizing and activating the coal gangue in sequence to obtain porous carbon; 2) dissolving boric acid and chitosan in an alcohol aqueous solution to obtain a mixed solution; immersing the obtained porous carbon in the mixed solution, and then heat-treating the mixture to obtain the composite negative electrode.
3. The flexible solid-state lithium-ion battery according to claim 2, characterized in that: The particle size of the coal gangue is 200-300 μm.
4. The flexible solid-state lithium-ion battery according to claim 2, characterized in that: The carbonization is carried out in an inert gas atmosphere, wherein the inert gas includes nitrogen; the carbonization temperature is 800-900°C, and the carbonization time is 1-3 hours; the activation includes: treating the carbonization product in an acid solution, wherein the acid solution includes one or more of acetic acid, hydrochloric acid and sulfuric acid, and the treatment time is 1-2 hours.
5. The flexible solid-state lithium-ion battery according to claim 2, characterized in that: The alcohol in the alcohol-water solution includes one or more of ethylene glycol, propylene glycol and butanediol; in the mixed solution, the mass fractions of the substances are: chitosan 2-4%, boric acid 2-4%, alcohol 60-85%, and the rest is water.
6. The flexible solid-state lithium-ion battery according to claim 2, characterized in that: The immersion time is 5-8 hours; the heat treatment temperature is 100-150° C., and the heat treatment time is 40-80 minutes.
7. The flexible solid-state lithium-ion battery according to claim 1, characterized in that: The conductive agent includes acetylene black, graphene or carbon fiber; the lithium salt includes lithium perchlorate and / or lithium tetrafluoroborate; and the binder includes polyvinylidene fluoride.
8. The method for preparing a flexible solid-state lithium-ion battery according to any one of claims 1 to 7, characterized in that: The steps include: (1) mixing a composite negative electrode, a conductive agent, a lithium salt, a binder and a solvent to obtain an electrode slurry, coating the electrode slurry on a copper foil to obtain a negative electrode sheet, depositing a diamond film on the negative electrode sheet and calcining it to obtain a solid negative electrode; (2) Take lithium foil, deposit a diamond film on the surface of the lithium foil and calcine it to obtain a solid positive electrode; (3) The solid-state negative electrode, the solid-state electrolyte and the solid-state positive electrode are stacked and assembled to obtain the flexible solid-state lithium-ion battery.
9. The preparation method according to claim 8, characterized in that: The solvent includes N-methylpyrrolidone; the mass volume ratio of the composite negative electrode, the conductive agent, the lithium salt, the binder and the solvent is 8-9g:1-2g:1-3g:2-3g:20-40mL; and the coating thickness is 30-60μm.
10. The preparation method according to claim 8, characterized in that: The deposition parameters are independently as follows: the deposition is carried out under a hydrogen atmosphere, the carbon sources are methane, ethanol and anisole, the volume ratio of methane, ethanol and anisole is 5-6:0.5-0.8:0.1-0.2, the flow rate of the carbon source is 15-30sccm, the surface temperature of the negative electrode sheet and the lithium foil during deposition is 700-800°C, the deposition pressure is 5-6kPa, and the deposition time is 1-2h; the calcination temperature is independently 800-900°C, and the calcination time is 30-80min.
Citation Information
Patent Citations
Lithium ion battery and preparation method thereof
CN106654350A
Manufacturing method of all solid state power lithium ion battery
CN108232318A
Method for improving interface of all-solid-state thin film secondary lithium ion battery positive electrode and electrolytic layer thin film
CN109301311A
Solid-state battery and manufacturing method thereof
CN112349956A
Preparation method of coal gangue-based red phosphorus doped C / SiOx composite lithium battery negative electrode material
CN115799502A